Case studies for advances in paleoimaging and other non-clinical applications - Beckett, Ronald G., 1953-; Conlogue, Gerald J.; Nelson, Andrew J. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2021)
"Case Studies for Advances in Paleoimaging and Other Non-Clinical Applications builds on the research and advances in technology, by looking at current and recent field case studies since the publication of the authors' pioneering book Paleoimaging: Field Applications for Cultural Remains and Artifacts"--
Case study 1: Large objects / Gerald Conlogue -- Case study 2: Zoological specimens / Gerald Conlogue, John Posh -- Case study 3: Skeletal remains / Gerald Conlogue, Andrew Nelson, Mark Viner, Alan Lurie, Alicia Giaimo -- Case study 4: Mummified remains / Gerald Conlogue, Ronald Beckett, John Posh, Mark Viner, Alan Lurie -- Case study 5: Manufactured or created objects: plane radiography / Gerald Conlogue, Robert Lombardo -- Case study 6: Teeth: plane radiography (Film); clinical CT; microCT / Andrew J. Nelson, Stan Kogon -- Case study 7: Contrast media injections / Gerald Conlogue, Ronald Beckett, John Posh, Bruce Young -- Case study 8: Endoscopy and XRF cases / Ronald Beckett and Gerald Conlogue.
OCLC-licensed vendor bibliographic record.
Keywords: Imaging systems in archaeology -- Case studies